N-acetylcysteine for prevention and treatment of COVID-19: Current state of evidence and future directions - José Luis Izquierdo-Alonso; Sandra Pérez-Rial; Carolina Gotera Rivera; Germán Peces-Barba (Elsevier, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes coronavirus disease 2019 (COVID-19) and can be associated with serious complications, including acute respiratory distress syndrome. This condition is accompanied by a massive release of cytokines, also denominated cytokine storm, development of systemic oxidative stress and a prothrombotic state. In this context, it has been proposed a role for acetylcysteine (NAC) in the management of patients with COVID-19. NAC is a molecule classically known for its mucolytic effect, but it also has direct and indirect antioxidant activity as a precursor of reduced glutathione. Other effects of NAC have also been described, such as modulating the immune and inflammatory response, counteracting the thrombotic state, and having an antiviral effect. The pharmacological activities of NAC and its effects on the mechanisms of disease progression make it a potential therapeutic agent for COVID-19. NAC is safe, tolerable, affordable, and easily available. Moreover, the antioxidant effects of the molecule may even prevent infection and play an important role as a complement to vaccination. Although the clinical efficacy and dosing regimens of NAC have been evaluated in the clinical setting with small series of patients, the results are promising. In this article, we review the pathogenesis of SARS-CoV-2 infection and the current knowledge of the mechanisms of action of NAC across disease stages. We also propose NAC posology strategies to manage COVID-19 patients in different clinical scenarios.